Adaptation of Escherichia coli to the mouse gut - Batista, João Miguel Barroso (2019)
The adaptation of organisms to the environment is a pervasive process in nature, which has been studied from the theoretical and experimental perspective over the years. Despite the plethora of in vitro studies addressing this subject, the adaptive process of individuals to a relevant natural environment is an area less explored. The mammalian gut, as a natural habitat inhabited by a complex cohort of microorganisms named the microbiota, represents a relevant host environment to study the adaption of commensal bacteria. However, the dynamics of adaptation of a commensal species in this environment are still poorly studied.(...)